HUBUNGAN KOMUNIKASI TERAPEUTIK PERAWAT DENGAN KEPUASAN PASIEN RAWAT INAP DI PUSKESMAS WOTU KABUPATEN LUWU TIMUR - Helmy kahar achmad; Wahidin Wahidin; Halim Halim (Jurnal Administrasi Negara, 2019)
One of the factors that affects patient satisfaction in health care is the communication done by healthcare personnel. The purpose of this research is to analyse the therapeutic communication relationship of nurses from the aspect of openness, empathy, nursing support, positive attitudes of nurses and equality between nurses and patients with the satisfaction of inpatient patients in Wotu Puskesmas Luwu Timur district. the type of research is analytical observational research, with cross sectional study design. The population and samples in this study were 87 respondents (saturated samples) with Purposive Sampling technique. The results of this study showed that the therapeutic communication of nurses from the aspect of openness, empathy, nursing support, positive attitudes of nurses and equality between nurses and patients are linked closely to the patient satisfaction in Wotu Puskesmas. The Wotu Puskesmas can increase patient satisfaction by increasing the skills of nurses in the Wotu Puskesmas inpatient installation.